Systemic oxidative–nitrosative–inflammatory stress during acute exercise in hypoxia; implications for microvascular oxygenation and aerobic capacity. Issue 12 (24th November 2014) - Woodside, John D. S.; Gutowski, Mariusz; Fall, Lewis; James, Philip E.; McEneny, Jane; Young, Ian S.; Ogoh, Shigehiko; Bailey, Damian M.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Exercise performance is limited during hypoxia by a critical reduction in cerebral and skeletal tissue oxygenation. To what extent an elevation in systemic free radical accumulation contributes to microvascular deoxygenation and the corresponding reduction in maximal aerobic capacity remains unknown. What is the main finding and its importance? We show that altered free radical metabolism is not a limiting factor for exercise performance in hypoxia, providing important insight into the fundamental mechanisms involved in the control of vascular oxygen transport. Exercise performance in hypoxia may be limited by a critical reduction in cerebral and skeletal tissue oxygenation, although the underlying mechanisms remain unclear. We examined whether increased systemic free radical accumulation during hypoxia would be associated with elevated microvascular deoxygenation and reduced maximal aerobic capacity (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m42sbc2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2 max </alternatives>). Eleven healthy men were randomly assigned single‐blind to an incremental semi‐recumbent cycling test to determine <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m42sf8z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2 max </alternatives> in both normoxia (21% O2) and hypoxia (12% O2) separated by a week. Continuous‐wave near‐infrared spectroscopy was employed to monitor concentration changes in oxy‐ and deoxyhaemoglobin in the left vastus lateralis muscle and frontal cerebral cortex. Antecubital venous blood samples were obtained at rest and at <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m42sf7d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2 max </alternatives> to determine oxidative (ascorbate radical by electron paramagnetic resonance spectroscopy), nitrosative (nitric oxide metabolites by ozone‐based chemiluminescence and 3‐nitrotyrosine by enzyme‐linked immunosorbent assay) and inflammatory stress biomarkers (soluble intercellular/vascular cell adhesion 1 molecules by enzyme‐linked immunosorbent assay). Hypoxia was associated with increased cerebral and muscle tissue deoxygenation and lower <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m42sfb2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2 max </alternatives> (P < 0.05 versus normoxia). Despite an exercise‐induced increase in oxidative–nitrosative–inflammatory stress, hypoxia per se did not have an additive effect (P > 0.05 versus normoxia). Consequently, we failed to observe correlations between any metabolic, haemodynamic and cardiorespiratory parameters (P > 0.05). Collectively, these findings suggest that altered free radical metabolism cannot explain the elevated microvascular deoxygenation and corresponding lower <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m42sf9h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V̇O2 max </alternatives> in hypoxia. Further research is required to determine whether free radicals when present in excess do indeed contribute to the premature termination of exercise in hypoxia.